Evaluación de las prácticas verdes en restaurantes y su influencia en la imagen percibida de los clientes en la ciudad de Portoviejo - Andrade Falcones, Gema Lisbeth (2019)
The objective of this research was to carry out the evaluation of green practices and their influence on the perceived image of customers in restaurants in the Portoviejo city, in order to comply with the investigation, three methodological phases were executed, first the identification was carried out of the variables about green practices and the perceived image, through the collection of bibliographic information that allowed identifying the indicators of the aforementioned variables, which are: energy efficiency and conservation, water efficiency and conservation, recycling, reduction of waste, employee education, green purchase, green image, green satisfaction, green confidence, green loyalty, perceived green risk, local products, organic products with respect to green practices, while for perceived image they are food quality, food flavor, food color, food aroma, healthy food and nutritive, quantity / portion, restaurant facilities, cleaning, internal / external design is aware of the concept of the restaurant, the menu and presentation inside and outside the restaurant is visually attractive, quality / price ratio, sustainability, use of materials environment friendly. In the second phase, the current status of the variables under study was determined, in which an interview was applied to business owners and a structured Ad Hoc survey with a Likert scale, to a sample of clients who visited restaurants every week, analyzing the results obtained through the SPSS program. And in order to carry out the last phase, the correlation between the green practices with respect to the perceived image was made, which allowed to know in what measures the environmental practices are being applied in the restaurants.